1998
DOI: 10.1007/s004180050275
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of annexins I, II and IV in human tissues: an immunohistochemical study

Abstract: Annexins constitute a family of Ca2+- and phospholipid-binding proteins. Although their functions are still not clearly defined, several members of the annexin family have been implicated in membrane-related events along exocytotic and endocytotic pathways. To elucidate a possible correlation of those functional proposals with the tissue distribution of annexins, we analysed immunohistochemically the expression of annexins I, II and IV in a broad variety of human tissues. Annexins I and II were chosen for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
94
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 58 publications
14
94
1
Order By: Relevance
“…The annexins belong to a family of multifunctional, calciumdependent, phospholipid-binding proteins (18). Prior studies have shown that, in the lung, annexins I and II were expressed in cilia and pleural mesothelial cells but not in Clara cells (19). Annexin I but not annexin II was found to be expressed in epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…The annexins belong to a family of multifunctional, calciumdependent, phospholipid-binding proteins (18). Prior studies have shown that, in the lung, annexins I and II were expressed in cilia and pleural mesothelial cells but not in Clara cells (19). Annexin I but not annexin II was found to be expressed in epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…The ANX2 heterotetramer acts as a receptor for plasminogen, tissue-type plasminogen activator and tenascin C, and is implicated in extracellular matrix degradation (Gerke et al, 2005). The ANX2 is not observed in normal hepatocytes, the pancreatic exocrine system and the mammary gland (Frohlich et al, 1990;Dreier et al, 1998;MasseyHarroche et al, 1998); in tumours that arise from these tissues, such as hepatocellular carcinoma, pancreatic cancer and breast cancer, respectively, ANX2 expression is observed as membrane and/or cytoplasmic staining (Frohlich et al, 1990;Diaz et al, 2004;Sharma et al, 2006). Esposito et al (Esposito et al, 2006) reported that ANX2 expression changed from cytoplasmic to cell surface expression with progression of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal liver, moderate expression of different annexins has been reported in the cytoplasm, bile duct, nuclear membrane, hepatocytes, and Kupffer cells. 45 Annexin A2 was immunolocalized in the bile duct but not in hepatocytes in the normal liver. 45 Immunofluorescence showed a marked increase in the expression of annexin A2 protein in human ALD at the hepatocyte cell surface, proliferating bile ducts, and in other small liver cells (Figure 7).…”
Section: Annexin A2mentioning
confidence: 94%
“…45 Annexin A2 was immunolocalized in the bile duct but not in hepatocytes in the normal liver. 45 Immunofluorescence showed a marked increase in the expression of annexin A2 protein in human ALD at the hepatocyte cell surface, proliferating bile ducts, and in other small liver cells (Figure 7). The Veterans Affairs Cooperative study 46 on alcoholic hepatitis reported proliferation of interlobular and marginal bile ducts with metaplasia and cells resembling oval cells in 122 human biopsy samples.…”
Section: Annexin A2mentioning
confidence: 94%